The Incidence and Causes of Unplanned Reoperations as a Quality Indicator in Pediatric Surgery - Miro Jukić; Ivona Biuk; Zenon Pogorelić (MDPI AG, 2022)
Background: Unplanned return to the operating room (uROR) within the 30-day postoperative period can be used as a quality indicator in pediatric surgery. The aim of this study was to investigate and evaluate uROR as a quality indicator. Methods: The case records of pediatric patients who underwent reoperation within the 30-day period after primary surgery, from 1 January 2018 to 31 December 2020 were retrospectively reviewed. The primary outcome of the study was the rate of uROR as a quality indicator in pediatric surgery. Secondary outcomes were indications for primary and secondary surgery, types and management of complications, factors that led to uROR, length of hospital stay, duration of surgery and anesthesia, and starting time of surgery. Results: A total of 3982 surgical procedures, under general anesthesia, were performed during the three-year study period (2018, n = 1432; 2019, n = 1435; 2020, n = 1115). Elective and emergency surgeries were performed in 3032 (76.1%) and 950 (23.9%) patients, respectively. During the study period 19 (0.5%) pediatric patients, with the median age of 11 years (IQR 3, 16), underwent uROR within the 30-day postoperative period. The uROR incidence was 6 (0.4%), 6 (0.4%), and 7 (0.6%) for years 2018, 2019, and 2020, respectively (p = 0.697). The incidence of uROR was significantly higher in males (n = 14; 73.7%) than in females (n = 5; 26.3%) (p = 0.002). The share of unplanned reoperations in studied period was 4.5 times higher in primarily emergency surgeries compared to primarily elective surgeries (p < 0.001). The difference in incidence was 0.9% (95% CI, 0.4-1.4). Out of children that underwent uROR within the 30-day period after elective procedures, 50% had American Society of Anesthesiologists (ASA) score three or higher (p = 0.016). The most common procedure which led to uROR was appendectomy (n = 5, 26.3%) while the errors in surgical technique were the most common cause for uROR (n = 11, 57.9%). Conclusion: Unplanned reoperations within the 30-day period after the initial surgical procedure can be a good quality indicator in pediatric surgery. Risk factors associated with uROR are emergency surgery, male gender, and ASA score ≥3 in elective pediatric surgery.